Bacille Calmette-Guérin Vaccine Strain Modulates the Ontogeny of Both Mycobacterial-Specific and Heterologous T Cell Immunity to Vaccination in Infants - Kiravu, Agano; Osawe, Sophia; Happel, Anna-Ursula; Nundalall, Trishana; Wendoh, Jerome; Beer, Sophie; Dontsa, Nobomi; Alinde, Olatogni Berenice; Mohammed, Sikiratu; Datong, Pam; Cameron, D. William; Rosenthal, Kenneth; et al. (Frontiers in Immunology, 2019)
Differences in Bacille Calmette-Guerin (BCG) immunogenicity and efficacy have been reported, but various strains of BCG are administered worldwide. Since BCG immunization may also provide protection against off-target antigens, we sought to identify the impact of different BCG strains on the ontogeny of vaccine-specific and heterologous vaccine immunogenicity in the first 9 months of life, utilizing two African birth cohorts. A total of 270 infants were studied: 84 from Jos, Nigeria (vaccinated with BCG-Bulgaria) and 187 from Cape Town, South Africa (154 vaccinated with BCG-Denmark and 33 with BCG-Russia). Infant whole blood was taken at birth, 7, 15 and 36 weeks and short-term stimulated (12 hour) in vitro with BCG, Tetanus and Pertussis antigens. Using multiparameter flow cytometry, CD4+ T cell memory subset polyfunctionality was measured by analyzing permutations of TNF-α, IL-2 and IFN- expression at each time point. Data was analyzed using FlowJo, SPICE, R and COMPASS. We found that infants vaccinated with BCG-Denmark mounted significantly higher frequencies of BCG-stimulated CD4+ T cell responses, peaking at week 7 after immunization, and possessed durable polyfunctional CD4+ T cells that were in a more early differentiated memory stage when compared with either BCG-Bulgaria and BCG-Russia strains. The latter responses had lower polyfunctional scores and tended to accumulate in a CD4+ T cell naïve-like state (CD45RA+CD27+). Notably, BCG-Denmark immunization resulted in higher magnitudes and polyfunctional cytokine responses to heterologous vaccine antigens (Tetanus and Pertussis). Collectively, our data show that BCG strain was the strongest determinant of both BCG-stimulated and heterologous vaccine stimulated T cell magnitude and polyfunctionality. These findings have implications for vaccine policy makers, manufacturers and programs worldwide and also suggest that BCG-Denmark, the first vaccine received in many African infants, has both specific and off-target effects in the first few months of life, which may provide an immune priming benefit to other EPI vaccines.